Law and Leviathan - Sunstein, Cass R.; Vermeule, Adrian (Cambridge, MA : Harvard University Press, 2020)
From two legal luminaries, a highly original framework for restoring confidence in a government bureaucracy increasingly derided as “the deep state.”Is the modern administrative state illegitimate? Unconstitutional? Unaccountable? Dangerous? Intolerable? American public law has long been riven by a persistent, serious conflict, a kind of low-grade cold war, over these questions.Cass Sunstein and Adrian Vermeule argue that the administrative state can be redeemed, as long as public officials are constrained by what they call the morality of administrative law. Law and Leviathan elaborates a number of principles that underlie this moral regime. Officials who respect that morality never fail to make rules in the first place. They ensure transparency, so that people are made aware of the rules with which they must comply. They never abuse retroactivity, so that people can rely on current rules, which are not under constant threat of change. They make rules that are understandable and avoid issuing rules that contradict each other.These principles may seem simple, but they have a great deal of power. Already, without explicit enunciation, they limit the activities of administrative agencies every day. But we can aspire for better. In more robust form, these principles could address many of the concerns that have critics of the administrative state mourning what they see as the demise of the rule of law. The bureaucratic Leviathan may be an inescapable reality of complex modern democracies, but Sunstein and Vermeule show how we can at last make peace between those who accept its necessity and those who yearn for its downfall.
Frontmatter -- Contents -- Introduction: “Long-Continued and Hard-Fought Contentions” -- 1 The New Coke -- 2 Law’s Morality, 1. Rules and Discretion -- 3 Law’s Morality, 2. Consistency and Reliance -- 4 Law’s Morality, 3. Limits, Trade-offs, and the Judicial Role -- 5 Surrogate Safeguards in Action -- Final Words -- Notes -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Nov 2020)
Keywords: Administrative agencies -- United States; Administrative discretion -- United States; Government accountability -- United States; LAW / Administrative Law & Regulatory Practice